Matematyka
gretka1212
2021-06-23 20:19:07
Potęgi :  (-2x^3y^2 : 2c ) ^2 = (x^10*x^2) * (x^3) ^2  kreska ułamkowa 3^2*x^2*x^5 =  (3^5*(1 1/3)^5 ) * (0,25^5:(1/2)^5) = (2^-2 + 2^-3 ) ^ -1 = (3x)^3*(x^3)^2:3^2*x^2*x^2 =
Odpowiedź
mazy12310
2021-06-24 01:26:22

[latex](-2x^3y^2 : 2c )^2=left( frac{-2x^3y^2}{2c} ight)^2=left( frac{-x^3y^2}{c} ight)^2= frac{x^6y^4}{c^2}[/latex] [latex]frac{(x^{10}cdot x^2)cdot (x^3) ^2}{3^2cdot x^2cdot x^5}= frac{x^{12}cdot x^6}{9cdot x^7}=frac{x^{18}}{9cdot x^7}=frac{x^{11}}{9}[/latex] [latex](3^5cdot (1 frac{1}{3} )^5 )cdot (0,25^5:( frac{1}{2} )^5)=[/latex] [latex](3^5cdot (frac{4}{3} )^5 )cdot (0,25^5:0,5^5)=[/latex] [latex](3^5cdot frac{4^5}{3^5} )cdot (0,25:0,5)^5=[/latex] [latex]4^5cdot 0,5^5=(4cdot 0,5)^5=2^5=32[/latex] [latex](2^{-2} + 2^{-3} ) ^ {-1}=left( left( frac{1}{2} ight) ^{2} + left( frac{1}{2} ight) ^{3} ight)^ {-1}=left( frac{1}{4}+ frac{1}{8} ight)^{-1}=[/latex] [latex]left( frac{2}{8}+ frac{1}{8} ight)^{-1}=left( frac{3}{8} ight)^{-1}= frac{8}{3}=2 frac{2}{3}[/latex] [latex](3x)^3 cdot (x^3)^2:3^2 cdot x^2 cdot x^2 =[/latex] [latex]27x^3 cdot x^6:9cdot x^2 cdot x^2 =[/latex] [latex]27x^9:9cdot x^2 cdot x^2 =[/latex] [latex]3x^9 cdot x^2 cdot x^2 =3x^{13}[/latex]

Dodaj swoją odpowiedź